2012
DOI: 10.3109/14015439.2012.664654
|View full text |Cite
|
Sign up to set email alerts
|

Voice onset time in Swedish children and adults

Abstract: Voice onset time (VOT) is a temporal acoustic parameter, which reflects the timing of speech motor control. The objective of the work was to obtain normative VOT-data in Swedish children. Thus, 150 children aged 8-11 years old and 36 adults were audio-recorded when producing the plosives in minimal pairs. Measures were made using waveforms and spectrograms. Results show that Swedish children developed adult-like VOT-values between 9 and 10 years. By the age of ten, prevoicing was also found fully adult like in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…Furthermore, in typically developed children, when prevoicing was well established it was present for all plosives in most cases (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in typically developed children, when prevoicing was well established it was present for all plosives in most cases (13).…”
Section: Discussionmentioning
confidence: 99%
“…VOT-values above or below one standard deviation from the mean value for the typically developed children in Larsson and Wiman, (15) and Lundeborg, et al (13) were considered as deviant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prior distributions for the posterior-predictive-density analysis were based on a published summary of VOT measurements, and on formant measurements from a database of recordings of Swedish speakers. Lundeborg et al (2012) reported VOT measurements on Swedish plosives. They found no significant difference between men and women and therefore reported the pooled results.…”
Section: Likelihood-ratio Calculationmentioning
confidence: 98%
“…폐쇄음은 입술, 혀, 턱, 후두 사이의 세밀한 협응을 통해서 산출되기 때문에, 음성 제어 능 력을 폐쇄음으로 VOT를 측정할 수 있다고 알려져 있다 (Auzou et al, 2000). Koenig(2000) 폐쇄음의 조음위치는 VOT값에 영향을 미치는 것으로 보고 되며, 선행 연구 (Bona & Auszmann, 2014;Cho et al, 2002;Lundeborg et al, 2012;Han, 2013 (Broersma, 2010;Rami et al, 1999;Shin, 2010). Rami 외 (Kent, 1976;Kummer, 2014).…”
Section: 서론 성대진동개시시간(Voice Onset Time; Vot 이하 Vot)은 폐 쇄음 파열 이후부터 모음이unclassified